Usability, Design, and Content Issues of Mobile Apps for Indonesia Cultural Art Promotion: A Balinese Mask - Jonata Witabora; Kadek Satria Adidharma; Laura Christina Luzar; Meilani Meilani; Nick Soedarso (Humaniora, 2016)
Various ways had been taken to promote the Indonesian culture in conventional media such as magazines, books, and even articles. The receiver generation who had lived in the abundance of technological world of digital media was the next target of inheritance and one way to do it was with the mobile application technology. So, it would be nice if the society started to take a big step to be more focused in the dissemination of culture and pass it following the development of the time, of course, without losing national identity. One of many interesting Indonesian Culture was Topeng Bali (Balinese Mask). Through observation and field research, knowledge about the art of Balinese mask was gathered, and later present it in form of mobile application. This research used the qualitative and quantitative method. The qualitative research was done by collecting data sampling from some of the selected target markets in limited quantities, while quantitative research was done by spreading the questionnaires that will be created and distributed to the main target market but not in the number and selected resource persons. This research finds that the mobile application is deemed appropriate to be one medium that can distribute effectively and efficiently in promoting one of Indonesia culture, Balinese mask.